Visi global : antisipasi Indonesia memasuki abad ke-21 - Budiman, Arief, 1941-; Aziz, Yaya M. Abdul, 1964- (Yogyakarta : Pustaka Pelajar, 1998)
Economic conditions, economic policies, Indonesia and international competition
Includes bibliographical references and index
Keywords: Competition, International; Indonesia -- Economic conditions -- 1945-; Indonesia -- Economic policy